2006
DOI: 10.1110/ps.062261606
|View full text |Cite
|
Sign up to set email alerts
|

Binding and signaling of surface‐immobilized reagentless fluorescent biosensors derived from periplasmic binding proteins

Abstract: Development of biosensor devices typically requires incorporation of themolecular recognition element into as olid surface for interfacing with as ignal detector.O ne approach is to immobilize the signal transducingp rotein directlyo nasolids urface. Herew ec ompare the effects of two directi mmobilization methods on ligand binding, kinetics, ands ignal transduction of reagentless fluorescent biosensors based on engineeredperiplasmic binding proteins. We used thermostable ribose andglucose binding proteins clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Subsequently, the binding of glucose to GBP induces a conformational change which may apparently bring closer both these two fluorescent proteins and therefore there is an increase in FRET efficiency. Several research workers have reported that FRET is apparently a very complex process when free and immobilized whole-cells or cell-free extracts are involved [19][20][21][22]. Regarding the differences in FRET efficiencies between the free and immobilized nanosensors, there are a number of factors affecting immobilized and soluble proteins such as restricted mobility on immobilization, chemical modification due to the immobilization method used, nature of the microenvironment and diffusion limitation [20].…”
Section: Glucose Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the binding of glucose to GBP induces a conformational change which may apparently bring closer both these two fluorescent proteins and therefore there is an increase in FRET efficiency. Several research workers have reported that FRET is apparently a very complex process when free and immobilized whole-cells or cell-free extracts are involved [19][20][21][22]. Regarding the differences in FRET efficiencies between the free and immobilized nanosensors, there are a number of factors affecting immobilized and soluble proteins such as restricted mobility on immobilization, chemical modification due to the immobilization method used, nature of the microenvironment and diffusion limitation [20].…”
Section: Glucose Assaymentioning
confidence: 99%
“…Apparently, this difference may be due to the reduced flexibility of the linker domain between the fluorescent proteins because of the attachment to solid surface. This issue emphasizes the importance to retain flexibility of both the fusion proteins in devising FRET pairs for immobilization to solid surfaces [19,21]. In general, FRET theory assumes that in a FRET couple only a single donor and a single acceptor are present with very weak coupling.…”
Section: Glucose Assaymentioning
confidence: 99%
“…Enzymes are very specific, however in some cases the catalysis is not desirable, thus some enzymes have to be modified to impair the activity and conserve only the ligand binding property, or the ideal case is to use a protein that only bind the analyte to monitor. Accordingly, a family of proteins in the periplasmic space of bacteria fulfill the last requirement (Looger, Dwyer et al 2003;de Lorimier, Tian et al 2006). These proteins named periplasmic binding proteins (PBPs), present a conformational change upon ligand binding, as a first step to interact with a membrane transporters (ABC proteins), previous of the translocation of ligand to the interior to the cell (de Lorimier, Tian et al 2006;Medintz and Deschamps 2006;Tsukiji, Miyagawa et al 2009).…”
Section: General Design Of Biosensormentioning
confidence: 99%
“…Accordingly, a family of proteins in the periplasmic space of bacteria fulfill the last requirement (Looger, Dwyer et al 2003;de Lorimier, Tian et al 2006). These proteins named periplasmic binding proteins (PBPs), present a conformational change upon ligand binding, as a first step to interact with a membrane transporters (ABC proteins), previous of the translocation of ligand to the interior to the cell (de Lorimier, Tian et al 2006;Medintz and Deschamps 2006;Tsukiji, Miyagawa et al 2009). The different members of these proteins are able to bind a large number of analytes, such a as: carbohydrates, amino acids, ions, hormones, heme-groups, etc.…”
Section: General Design Of Biosensormentioning
confidence: 99%
“…As such, it has been expected to be a suitable sensing element for blood or intracellular glucose monitoring. Indeed, there have been several reports about fluorescentbased glucose-sensing systems using GBP conjugated with fluorophores that change in fluorescent intensity with a GBP conformational change (de Lorimier et al, 2002;Der and Dattelbaum, 2008;Salins et al, 2001;Thomas et al, 2006;Tolosa et al, 1999), and also about the design of FRET-based methods using GBP (de Lorimier et al, 2006;Deuschle et al, 2005;Fehr et al, 2003Fehr et al, , 2005Ge et al, 2004;Khan et al, 2008), which allow glucose sensing in vitro and also in mammalian cells. We have been engaged in the development of glucose-sensing molecules with GBP such a glucosespecific SBP with a K d value suitable for the measurement of physiological glucose concentrations and a novel luminescence-based glucose-sensing molecule combining with a luciferase (Taneoka et al, 2009).…”
Section: Introductionmentioning
confidence: 99%